Combination of Thulium Laser Incision and Bipolar Resection Offers Higher Resection Velocity than Bipolar Resection Alone in Large Prostates - Huang, Kuan Chun; Chow, Yung Chiong; Chen, Marcelo; Chiu, Allen W. (Urology Journal, 2019)
Purpose: We compared the efficacy and safety of a combined thulium laser incision and bipolar resection of prostate technique (web procedure) with traditional bipolar TURP. Materials and Methods: We reviewed the medical records of 96 web procedure, 93 traditional bipolar TURP patients between 2013 and 2016. The web procedure consisted of thulium laser incision of the prostate at 3, 5, 7, 9 and 12 o’clock positions up to the resection plane and subsequent bipolar resection of the created prostate blocks. Resected tissue weight, operative time, resection velocity, complications, blood loss, and early operative outcome were compared. Results: No significant differences were noted among the web procedure (web group) and traditional bipolar TURP in preoperative PSA ( 6.3 vs 8.7 ng/mL, P =0.295), preoperative postvoid residual urine (55.1 vs 76.4, P =.056), modified hemoglobin decrease (defined as total Hb decrease divided by the weight of the resected tissue: 0.060 vs 0.051, p=.380), complication rate (5.2% vs 5.3 %, P =.958), hospitalization (4.0 vs 4.2 days, P =.120) and catheterization (2.5 vs 3.4, p=.066). The resection velocity was higher in the web group (0.23 vs 0.17 g/ min, p=.001). In subgroup analysis, the significant difference of resection velocity between two group was showed in large prostates (>40 g: 0.25 vs 0.20 g/min, P =0.02 ) but not in the small prostate group. There was no difference in postoperative postvoid residual urine (21.9 vs 30.3 P =.231) and postvoid residual urine decrease (33.1 vs 45.5, P = .167) 2 months after surgery. Conclusion: The combination thulium laser incision and bipolar TURP technique had a higher resection efficiency and comparable efficacy and safety than traditional bipolar TURP.